91.3k views
4 votes
Choose this correct simplification of the expression (-5a^5b^4c^3)^0.

a)1
b)0
c)5a^5b^4c^3
d)-5

User Mhrsalehi
by
4.9k points

2 Answers

5 votes
Trick question! Note that (anything)^0 = 1. So, certainly, (-5a^5b^4c^3)^0 = 1.
User Tony Abrams
by
5.0k points
3 votes

\bf \left( \cfrac{cheeseburger}{spaghetti} \right)^0=ducks^0=bologne^0=(15\cdot 25+3\cdot 100000)^0=1


anything whatsoever, with the sole exception of 0 itself, raised at the 0 power, is 1.
User Vitto
by
5.8k points